Effectiveness of Android-Based Educational Application on Increasing Pregnant Women's Knowledge about Basic Infant Immunization during the First 1000 Days of Life - Azis, Masyitha; Nurdin, Andi Armyn; Niswar, Muhammad (PINISI Discretion Review, 2024)
The immunization program for infants aims to ensure that every baby receives complete basic immunization, as each vaccine in the basic immunization series provides different benefits for the baby's body. This study aims to evaluate the effectiveness of an Android-based educational application in improving pregnant women's knowledge of basic infant immunizations during the First 1000 Days of Life. The study was conducted at Masyita Maternity Hospital in Makassar, using a quasi-experimental design with a sample of 40 primigravida pregnant women who met the research criteria. Respondents received an intervention in the form of an Android-based educational application, and their usage activity was monitored through a dashboard. Data were analyzed using cross-tabulation and the McNemar test. The results showed that the majority of respondents were aged 20-25 years (55%), from the Makassar ethnic group (60%), and in the second trimester of pregnancy (50%). The Android-based educational application was proven to be effective in improving pregnant women's knowledge of basic infant immunizations, with statistically significant results (p=0.01; p<0.05).